POTENSI PENGEMBANGAN TERNAK SAPI POTONG RAKYAT DI KECAMATAN RAINIS KABUPATEN KEPULAUAN TALAUD - Arny Sasoeng; Wenny Tilaar; Jolanda Kitsia Juliana Kalangi (Sam Ratulangi University, 2020)
This study aims to develop small-scale beef cattle in the Sub-district of Rainis, Talaud Islands Regency by analyzing the potential of existing land and animal feed, and to strive for the maintenance of cattle not not as a part-time business but rather a main business.This research was conducted in December 2019 until February 2020, in Rainis Sub-district, Talaud Islands Regency. Data collected in the form of primary data and secondary data. Primary data were collected by direct interviews with 40 respondents using a list of questions (questionnaire) and direct observation in the field. Secondary data were obtained from the Rainis District Office. The determination of the sample location of the study was determined purposively with consideration of the level of ownership of beef cattle in four villages namely Tabang Village, West Tabang Village, Bantane Village and North Bantane Village. Determination of the respondents is based on the criteria that the farmers are small-scale beef cattle farmers who have been raising cattle for more than 1 (one) year and have plantation land, and have sold cattle. Analysis of the data in this study is quantitative / statistical in order to test the hypothesis that has been set. The results showed that Rainis Sub-district, Talaud Island Regency had the potential for the development of beef cattle in terms of aspects of land availability for feed, human resources, and livestock productivity aspects of animal health, facilities and infrastructure aspects, socio-cultural aspects, economic aspects of farmers who run Coconut farming by integrating with people's beef cattle gets an average income of Rp. 41.497.742// respondent / year and aspects of market opportunities.*eprm*